2020
DOI: 10.1007/s40121-020-00323-4
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Review of Meningococcal Disease Burden in India

Abstract: Introduction: Meningococcal disease caused by Neisseria meningitidis has a high case fatality rate. Of 12 distinct serogroups, A, B, C, W-135 (W) and Y cause the majority of infections. The meningococcal disease burden and epidemiology in India are not reliably known. Hence, we performed a narrative review with a systematically conducted search to summarize information on meningococcal disease burden and epidemiology and vaccination recommendations for meningococcal disease in India.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 44 publications
2
18
0
Order By: Relevance
“…IMD is recognized as a notifiable disease in India and a recent literature review concluded there is a significant burden of meningococcal disease-related complications in this country. 21 The review also found that meningococcal disease is increasingly reported among adolescents and adults, with large outbreaks described in these populations, the most recent of which occurred in Meghalaya 58 and Tripura. 59 The Meghalaya outbreak occurred from January 2008 until June 2009 with 110 cases aged up to 18 years and seven deaths from one center as per the study by Hazarika et al, 58 whereas the total number of cases in the state were 2100 with 260 deaths.…”
Section: Epidemiology Of Meningococcal Disease In Indiamentioning
confidence: 98%
See 4 more Smart Citations
“…IMD is recognized as a notifiable disease in India and a recent literature review concluded there is a significant burden of meningococcal disease-related complications in this country. 21 The review also found that meningococcal disease is increasingly reported among adolescents and adults, with large outbreaks described in these populations, the most recent of which occurred in Meghalaya 58 and Tripura. 59 The Meghalaya outbreak occurred from January 2008 until June 2009 with 110 cases aged up to 18 years and seven deaths from one center as per the study by Hazarika et al, 58 whereas the total number of cases in the state were 2100 with 260 deaths.…”
Section: Epidemiology Of Meningococcal Disease In Indiamentioning
confidence: 98%
“…58,59 Meningococcal disease in India appears to be caused almost exclusively by serogroup A, although serogroups B, C, W, and Y have also been documented. 21 Further epidemiological information is also available from the military in India. In 2005-2010, the Indian Armed Forces had an average attack rate of 9 or 10 cases of meningococcal disease per year and the N. meningitidis carrier rate among recruits was estimated in the 1990s to be 12%.…”
Section: Epidemiology Of Meningococcal Disease In Indiamentioning
confidence: 99%
See 3 more Smart Citations